Persistence of antibody after accelerated immunisation with diphtheria/tetanus/pertussis vaccine. - Ramsay, M E (1991)
OBJECTIVE--To determine the persistence of antibody to diphtheria, tetanus, and pertussis in children receiving an accelerated schedule of primary immunisation. DESIGN--Controlled study of antibody testing of blood samples from children immunised according to various schedules: three doses of triple vaccine completed at 8-13 calendar months, 6-7 calendar months, before 6 calendar months, or three doses followed by diphtheria/tetanus before age 2. SETTING--Plymouth Health Authority. SUBJECTS--129 children aged 4 years who had received three doses of diphtheria/tetanus/pertussis vaccine with or without a diphtheria/tetanus booster. MAIN OUTCOME MEASURES--Diphtheria and tetanus antitoxin concentrations and antibody titres to pertussis toxin, filamentous haemagglutinin, and agglutinogens 2 and 3. RESULTS--All children had protective concentrations of antitoxin to diphtheria and tetanus (greater than or equal to 0.01 IU/ml). There was no evidence of a significant difference in diphtheria or tetanus antitoxin concentrations and pertussis antibody titres in children immunised with an accelerated course (third dose of triple vaccine before 6 months) compared with those who received a longer course (third dose at 8-13 months) with no booster (geometric mean antitoxin concentration 0.411 (95% confidence interval 0.273 to 0.618) v 0.426 (0.294 to 0.616) for diphtheria and 0.358 (0.231 to 0.556) v 0.299 (0.197 to 0.453) for tetanus; geometric mean antibody titres 903 (500 to 1631) v 1386 (848 to 2266) for pertussis filamentous haemagglutinin, 179 (130 to 248) v 232 (167 to 322) for pertussis toxin, and 2002 (1276 to 3142) v 3591 (2220 to 5809) for agglutinogens 2 and 3). CONCLUSION--Immunisation with three doses of triple vaccine at monthly intervals completed before 6 months of age probably provides adequate protection against diphtheria, tetanus, and whooping cough which will persist until the age of the preschool booster.